The relationship between functional theory of attitudes and purchase intention of counterfeit luxury sunglasses: A moderated moderated-mediation conditional model. Issue 4 (2nd October 2022) - Singh, Anurag; Patel, Ashok Kumar; Parayitam, Satyanarayana
ABSTRACT: This study aims to empirically examine the effect of attitudinal functions: social-adjustive, value-expressive, ego-defensive, and product knowledge on consumer purchase intention for non-deceptive counterfeit Ray-Ban sunglasses. Most importantly, instead of direct relationships, we study the complex inter-relationships between these attitudinal functions on consumers' purchase intention of counterfeit products. The data were collected from 421 respondents from Eastern UP, India, and after checking the measurement properties of the survey instrument Hayes (2018) PROCESS was used to analyze the data. The results from the study indicate that (i) social-adjustive function is positively related to purchase intention, (ii) social adjustive function is positively related to product knowledge function, (iii) value expressive function moderates the relationship between product knowledge function and purchase intention, (iv) ego defensive function (second moderator) moderates the moderated relationship between social adjustive function and value expressive function (first moderator) mediated through product knowledge function. The results did not support the negative relationship between product knowledge and purchase intention of counterfeit Ray-Ban sunglasses. The present study has several implications for (i) the literature on consumers' behavior concerning counterfeit products, (ii) managers aiming to sell non-deceptive counterfeit products, and (iii) policy-making bodies and agencies concerning counterfeit products.